RELATIONSHIP AND LEGISLATIVE REGULATION OF THE CONCEPTS «ORGANIC PRODUCTS» AND «ENVIRMENTALLY FRIENDLY PRODUCT» (Journal of actual problems of jurisprudence, 2024)
The article was prepared within the framework of the grant project of the Ministry of Science and Higher Education of the Republic of Kazakhstan No. AP14870596 «Problems of legal regulation of rational use and protection of pasture ecosystems».In the National Security Strategy of the Republic of Kazakhstan for 2021-2025, signed by Head of State Tokayev Kassym-Jomart Kemelevich, priority is given to the sustainable development of the country's economy, including the agricultural sector, ensuring environmental, technological information, water and food security.«Food security» is an integral part of «national security». In accordance with Article 22 of the Law of the Republic of Kazakhstan «On the National Security of the Republic of Kazakhstan» «food security is a part of economic security and provides for the protection of the economy, including the agro-industrial complex, in which the state is able to provide physical and economic accessibility to the population of high-quality and safe food products, sufficient to meet the physiological norms of consumption and demographic growth». As noted in the definition, «quality» and «safe food» has already become one of the main issues in the country at this stage.Increasing the range and diversity of food production causes consumers to demand high quality and safety of food production. Recently, the concepts of product quality, safety, product certification are often heard inside the country, taking into account the requirements of consumers, a food culture has developed in society, and demand for environmentally friendly products is growing. Increasing competition in the country is directly related to improving the quality of products.The production of environmentally friendly products is regulated by the Law of the Republic of Kazakhstan dated November 27, 2015 «On the production of organic products» and the Law of the Republic of Kazakhstan dated November 27, 2015 «On amendments and additions to certain legislative acts of the Republic of Kazakhstan on the production of organic products and the development of the agro-industrial complex».Unfortunately, due to the lack of state standards for environmentally friendly products in the Law and the lack of a clear definition of the concept of «environmentally friendly products», there will be no consumer confidence in the quality of products manufactured on marketable goods of the brands «organic», «bio», «halal» and etc. The country needs to develop a market for standardization and certification of environmentally friendly products that meet international standards. The system of improving product quality, certification, standardization and control of products also requires attention from the state.In the article, the authors define the concepts of «environmentally friendly product» and «organic products», provide for their legislative regulation. Analyzing the specifics of ecological products from organic, they reveal the importance and possibilities of producing high-quality food products. Proposals will also be presented to improve legislation and standards governing relations in the food market, taking into account the quality and safety of agricultural products.Key words: organic products, environmentally friendly products, safety, market, certificate, brand, products, product quality